Constraints on the Higgs boson self-coupling from the combination of single and double Higgs boson production in proton-proton collisions at s=13TeV - A. Hayrapetyan; A. Tumasyan; W. Adam; J.W. Andrejkovic; T. Bergauer; S. Chatterjee; K. Damanakis; M. Dragicevic; P.S. Hussain; M. Jeitler; N. Krammer; A. Li; et al. (Physics Letters B)
The Higgs boson (H) trilinear self-coupling, λ3, is constrained via its measured properties and limits on the HH pair production using the proton-proton collision data collected by the CMS experiment at s=13TeV. The combination of event categories enriched in single-H and HH events is used to measure κλ, defined as the value of λ3 normalized to its standard model prediction, while simultaneously constraining the Higgs boson couplings to fermions and vector bosons. Values of κλ outside the interval −1.2<κλ<7.5 are excluded at 2σ confidence level, which is compatible with the expected range of −2.0<κλ<7.7 under the assumption that all other Higgs boson couplings are equal to their standard model predicted values. Relaxing the assumption on the Higgs couplings to fermions and vector bosons the observed (expected) κλ interval is constrained to be within −1.4<κλ<7.8 (−2.3<κλ<7.8) at 2σ confidence level.